Visual Enhancement of Aerial Flight in High Plateau Low Visibility Conditions - Xiao, Ying (International Journal of Computer Science and Information Technology, 2024)
A method for automatic detection of airport runways in low visibility, forward and downward looking aerial airport images is proposed. Firstly, the recursive Otsu segmentation method is used to extract the main contour of the airport from the complex background; then the morphological filtering is performed by using the morphology-based open and swell operations, the open operation is used to filter out the isolated noise points and the swell operation is used to connect the segmented airport components into a complete whole; finally, the morphological filtered image is subjected to the region growth to localize the main runway of the airport. Finally, the morphology filtered image is processed to localize the main airport runway by its region growth. It is proved that this method can quickly and accurately detect and localize the main and auxiliary runways of airports in low visibility and forward and downward looking aerial images of airports.